NETWORK-BASED BUSINESS MODEL INNOVATION IN ANIMATION INDUSTRY IN INDONESIA, CASE STUDY OF TRANS TV, CIMAHI CREATIVE ASSOCIATION, AND ELEX MEDIA - Fernando, Edwin; Dellyana, Dina (Journal of Business and Management, 2017)
Â Abstract. Animation industry is one of the fastest growing industries in the world with a market worth 12.01 billion dollars in 2017. Indonesia which has many cultures and large population has potential to develop animation industry. The major problem to develop the animation industry is the lacking information within actors and the rigid system in the network. This causes the innovation and value cannot be maximized in this industry. This research conducted to analyze the network characteristic, business model, business model innovation, and value outcome in animation industry network by using conceptual model of four dimension which are; network, business model, business model innovation, and value. This research is done by qualitative method by applying interview, observation, and secondary data. Three types of network are used as a case study, which are; vertical value net, horizontal value net, and multidimensional value net with case study of Trans TV (vertical value net), Cimahi Creative Association (horizontal value net), and Elex Media (multidimensional value net). The data is being compared with each network using cross-case analysis method using table. Trans TV and Elex Media using agreement control in the network, that causes business model innovation determined mostly by focal firm. While in Cimahi Creative Association using less control in the network that causes business model innovation determined fairly between focal actors and member. Each network has different value outcome depends on related network characteristic, business model, and business model innovation.Â Keywords: Animation Industry, Network, Business Model, Business Model Innovation, Value